Detection of Campylobacter jejuni and Campylobacter coli in Environmental Waters by PCR Enzyme-Linked Immunosorbent Assay - Sails, A. D. (American Society for Microbiology, 2002)
A PCR enzyme-linked immunosorbent assay (ELISA) assay was applied to the detection of Campylobacter jejuni and Campylobacter coli in environmental water samples after enrichment culture. Bacterial cells were concentrated from 69 environmental water samples by using filtration, and the filtrates were cultured in Campylobacter blood-free broth. After enrichment culture, DNA was extracted from the samples by using a rapid-boiling method, and the DNA extracts were used as a template in a PCR ELISA assay. A total of 51 samples were positive by either PCR ELISA or culture; of these, 43 were found to be positive by PCR ELISA and 43 were found to be positive by culture. Overall, including positive and negative results, 59 samples were concordant in both methods. Several samples were positive in the PCR ELISA assay but were culture negative; therefore, this assay may be able to detect sublethally damaged or viable nonculturable forms of campylobacters. The method is rapid and sensitive, and it significantly reduces the time needed for the detection of these important pathogens by 2 to 3 days.